2012
DOI: 10.1088/0004-637x/746/2/116
|View full text |Cite
|
Sign up to set email alerts
|

THE FERMI BUBBLE AS A SOURCE OF COSMIC RAYS IN THE ENERGY RANGE >1015eV

Abstract: The Fermi Large Area Telescope has recently discovered two giant gamma-ray bubbles that extend north and south of the Galactic center with diameters and heights of the order of H ∼ 10 kpc. We suggest that the periodic star capture processes by the Galactic supermassive black hole Sgr A * , with a capture rate of τ −1 cap ∼ 3 × 10 −5 yr −1 and an energy release of W ∼ 3 × 10 52 erg per capture, can result in hot plasma injecting into the Galactic halo at a wind velocity of u ∼ 10 8 cm s −1. The periodic injecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 82 publications
(102 reference statements)
2
48
0
Order By: Relevance
“…Given the very hard spectrum, a total power in these particles that approaches 10 39 erg s −1 , and that the particles are delivered into the halo but not too far above the disk, these shocks are interesting candidates (see Parizot 2014) for the main accelerators of Galactic cosmic rays in this energy range (see Cheng et al 2012;Lacki 2014;Taylor et al 2014).…”
Section: Further Speculationsmentioning
confidence: 99%
“…Given the very hard spectrum, a total power in these particles that approaches 10 39 erg s −1 , and that the particles are delivered into the halo but not too far above the disk, these shocks are interesting candidates (see Parizot 2014) for the main accelerators of Galactic cosmic rays in this energy range (see Cheng et al 2012;Lacki 2014;Taylor et al 2014).…”
Section: Further Speculationsmentioning
confidence: 99%
“…The sheer size of the Bubbles makes them excellent places for the acceleration of extremely high energy particles (c.f., Cheng et al 2012). Electrons are highly radiative particles, so their maximum energy is set by IC or synchrotron losses.…”
Section: Magnetic Fieldsmentioning
confidence: 99%
“…Smooth attachment of the spectra above and below this energy and sharpness of the transition indicates that we are dealing with a single spectrum rather than with the sum of two distinct components. The review of different models suggested to explain this phenomenon can be found in the original paper [17].…”
Section: Fermi Bubbles As Giant Re-acceleration Sitesmentioning
confidence: 99%